Thermal and phase behavior of didodecyldimethylammonium bromide aqueous dispersions - Feitosa, Elosi [UNESP]; Adati, Renata D. [UNESP]; Alves, Fernanda R. (Elsevier B.V., 2015)
This work aims to delineate the single isotropic vesicle phase (Ves) in the binary didodecyldimethylammonium bromide (DDAB)/water system, limited by the critical vesicle concentrations, CVC1 approximate to 0.05 mM (2.3 x 10(-3) wt%) and CVC2 approximate to 0.7 mM (3.1 x 10(-2) wt%), as the onset of unilamellar vesicle formation and of two-phase separation into Ves + Lam (lamellar) phases, respectively. Isothermal titration calorimetry (ITC), turbidity, and crossed polaroids observations indicate that below CVC1 the dispersion is dominated by free monomers or micelles, but rich in uni- and multilamellar vesicles between CVC1 and CVC2, with CVC2 = 0.21 mM (9.5 x 10(-3) wt%) being the onset of multilamellar vesicle formation. Above CVC2, the volume of the Lam phase increases, while the volume for the Ves phase decreases to vanish around CVC3 approximate to 21 mM (0.95 wt%). Differential scanning calorimetry (DSC) data show that the gel-to-liquid crystalline transition at T-m approximate to 16 degrees C is highly cooperative (Delta T-1/2 approximate to 0.3 degrees C), and the melting enthalpy (Delta H-m) increases with DDAB concentration. Because of the remarkably slow liquid crystalline-to-gel kinetics, a cooling transition around T-m' approximate to 9.5 degrees C is reported here for the first time, we ascribe to the liquidcrystallineto-gel transition (thermal hysteresis Delta T-m approximate to 6.5 degrees C). Vesicle and lamellar structure formation is supported also by hydrodynamic diameter (D-H) data, being 100-140 and 800-1200 nm, respectively, at 25 degrees C. The zeta potential (zeta) increases with DDAB concentration but does not change much with temperature, indicating no pronounced structural change when temperature varies around T-m. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Cationic vesicles; DDAB; Differential scanning calorimetry; Dynamic light scattering; Gel-liquid crystalline transitions; Zeta potentials